2020
DOI: 10.7150/ijbs.46966
|View full text |Cite
|
Sign up to set email alerts
|

The role of monoamine oxidase A in HPV-16 E7-induced epithelial-mesenchymal transition and HIF-1α protein accumulation in non-small cell lung cancer cells

Abstract: Our previous studies have found that human papillomavirus (HPV)-16 E7 oncoprotein promotes epithelial-mesenchymal transition (EMT) and hypoxia-inducible factor-1α (HIF-1α) protein accumulation in non-small cell lung cancer (NSCLC) cells and monoamine oxidase A (MAOA) is highly expressed in NSCLC tissues. Here, we further explored the role of MAOA in HPV-16 E7-induced EMT and HIF-1α protein accumulation in A549 and NCI-H460 NSCLC cells. Our results showed that HPV-16 E7 enhanced MAOA expression in NSCLC cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 51 publications
(78 reference statements)
0
26
0
Order By: Relevance
“…Tang's group found positive expression of MAOA in 9 out of 12 LUAD tumors by IHC ( 18 ). Recently, we reported that MAOA plays a critical role in NSLC migration and HPV-16 E7 induced-HIF-1α protein accumulation in NSCLC cells ( 17 ). Another group found that a potential inhibitor of MAOA, G11, increases the sensitivity of chemotherapy drug and metastasis of NSCLC cells ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tang's group found positive expression of MAOA in 9 out of 12 LUAD tumors by IHC ( 18 ). Recently, we reported that MAOA plays a critical role in NSLC migration and HPV-16 E7 induced-HIF-1α protein accumulation in NSCLC cells ( 17 ). Another group found that a potential inhibitor of MAOA, G11, increases the sensitivity of chemotherapy drug and metastasis of NSCLC cells ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we showed that MAOA abrogates cancer cell growth and serves as an independent biomarker for LUAD. Monoamine oxidase A was reported to be an oncogene in NSCLC (17,37). Tang's group found positive expression of MAOA in 9 out of 12 LUAD tumors by IHC (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, these changes were more obvious in the 1% oxygen concentration group than in the 5% oxygen concentration group in both LUSC and LUAD cells. is may be because, under hypoxic conditions, the transcriptional instability of tumor cells may cause the activation of some cancer survival-related factors, resulting in the enhancement of tumor migration and invasion and promotion of cancer development [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Given the fact that MAOA was reported as a key regulator of epithelial-to-mesenchymal transition (EMT) in multiple cancers [20], we herein also wondered whether PCa bone metastasis could be inhibited by targeting MAOA induced EMT. By detection of the expression of EMT markers, we found that in PC3-378OE cells treated with GW4869, the expression of E-cad was signi cantly upregulated along with a signi cant downregulation of N-cad and vimintin expression (Fig.…”
Section: Overexpression Of Mir-378a-3p Inhibits Epithelial-tomesenchymal Transition (Emt) For Metastasis By Targeting Maoamentioning
confidence: 99%